2021
DOI: 10.3389/fmicb.2021.705853
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Essential Genes Associated With Prodigiosin Production in Serratia marcescens FZSF02

Abstract: Prodigiosin is a promising secondary metabolite produced mainly by Serratia strains. To study the global regulatory mechanism of prodigiosin biosynthesis, a mutagenesis library containing 23,000 mutant clones was constructed with the EZ-Tn5 transposon, and 114 clones in the library showed altered prodigiosin production ability. For 37 of the 114 clones, transposon insertion occurred on the prodigiosin biosynthetic cluster genes; transposon inserted genes of the 77 clones belonged to 33 different outside prodig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
1
16
1
Order By: Relevance
“…EnvZ/OmpR is known to control motility (Prüß, 2017), intracellular survival (Du et al, 2022), antibiotic resistance (Ko and Choi, 2022), virulence (Tipton and Rather, 2017), and other characteristics of different bacterial strains, but few studies have reported the role of EnvZ/OmpR in S. marcescens. We have demonstrated previously that mutation of ompR or envZ would cause the loss of prodigiosin producing ability in S. marcescens FZSF02 and confirmed that the two-component system EnvZ/OmpR was a newly found system that can regulate prodigiosin biosynthesis (Jia et al, 2021). In this study, the regulatory function of EnvZ/OmpR on prodigiosin biosynthesis was further confirmed by gene deletion and complementation (Figure 1C).…”
Section: Discussionsupporting
confidence: 85%
“…EnvZ/OmpR is known to control motility (Prüß, 2017), intracellular survival (Du et al, 2022), antibiotic resistance (Ko and Choi, 2022), virulence (Tipton and Rather, 2017), and other characteristics of different bacterial strains, but few studies have reported the role of EnvZ/OmpR in S. marcescens. We have demonstrated previously that mutation of ompR or envZ would cause the loss of prodigiosin producing ability in S. marcescens FZSF02 and confirmed that the two-component system EnvZ/OmpR was a newly found system that can regulate prodigiosin biosynthesis (Jia et al, 2021). In this study, the regulatory function of EnvZ/OmpR on prodigiosin biosynthesis was further confirmed by gene deletion and complementation (Figure 1C).…”
Section: Discussionsupporting
confidence: 85%
“…Previously, we have reported that the spontaneous non-pigmented mutants showed similar pathogenicity to silkworm larvae as the wild-type strain S. marcescens ( Zhou et al, 2016b ). In addition, a mutation in T6SS was suggested involving S. marcescens pigment production by using Tn5-mutagenesis technology ( Jia et al, 2021 ). The downregulated T6SS might relate to the reduced prodigiosin production, or at least did not affect bacterial virulence.…”
Section: Discussionmentioning
confidence: 99%
“…LuxS/AI-2 often acts as a second quorum sensing system to control certain phenotypes ( Sun et al, 2016 ). The two-component systems RssB/RssA, PigQ/W, and EnvZ/OmpR also regulate prodigiosin production in Serratia species ( Fineran et al, 2005 ; Horng et al, 2010 ; Jia et al, 2021 ). It is worth noting that all these regulators may result in multiple unexpected phenotypic changes in Serratia , including biosurfactants, antibiotics and exoenzymes production, cell motility, and virulence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a key enzyme in the PG biosynthesis pathway, PigC presents a bottleneck for efficient broad-range prodiginine production because of its limited substrate acceptance [ 21 ]. Gene complementation confirmed the regulatory function of the EnvZ/OmpR two-component regulatory system of genes envZ and ompR in PG production [ 22 ]. The final complex protein-PG can be traced at 500 nm, but the maximum pure PG can be observed at 535 nm and also determined by characteristic bands using RAMAN spectroscopy [ 23 , 24 ].…”
Section: General Properties Of Prodigiosinmentioning
confidence: 98%